Clinical Utility of Ultrasound Imaging for Measuring Anterior Thigh Thickness after Anterior Cruciate Ligament Injury in an Individual Patient to Assess Postsurgery Outcome - Filippo Mechelli; Richard Bayford; Hemda Garelick; Maria Stokes; Sandra Agyapong-Badu (Case Reports in Orthopedics)
The present study investigated the clinical utility of ultrasound imaging (USI) for assessing changes in an individual’s quadriceps muscle and subcutaneous fat (SF) thickness of the anterior thigh and their relative proportions. A patient was studied prior to and after anterior cruciate ligament reconstruction (ACLR) surgery and during rehabilitation. This case study involved an 18-year-old female recreational athlete with a complete tear of the anterior cruciate ligament (ACL). Tissue thickness (SF and quadriceps muscle) was measured from transverse USI of the anterior thigh before surgery, at weekly intervals during 12 weeks of postsurgery, and then every 2 weeks for the following 12 weeks (total of 21 measurement sets). Statistically significant differences presurgery to postrehabilitation were found for muscle thickness (p=0.04) and SF tissue thickness (p=0.04) measurements. There was no difference in muscle to fat ratio (p=0.08). Changes in measurements greater than the reported minimal detectable change (MDC) demonstrate the sensitivity of the USI technique as an objective tool to assess clinically useful changes in an individual’s anterior thigh muscle thickness post-ACLR surgery and during rehabilitation.